PENGEMBANGAN DESAIN DAN PRODUK FURNITUR EDUKASI UNTUK PENYANDANG CEREBRAL PALSY DI YPK BALI - Wahyudi Linggasani, Made Anggita; Putu Gede Suranata; I Wayan Yogik Adnyana Putra; Gde Bagus Andhika Wicaksana (Jurnal Abdi Masyarakat, 2025)
This community service program aimed to improve the rehabilitation services for individuals with cerebral palsy at Yayasan Peduli Kemanusiaan (YPK) Bali by designing and producing adaptive furniture that is ergonomic, affordable, and tailored to user needs. Identified problems included non-ergonomic tools, limited availability of adaptive devices, high cost, lack of inclusive design expertise, and limited collaboration with academic institutions. Using User-Centered Design (UCD) and Participatory Action Research (PAR) methods, the team developed a rehabilitation chair and an ergonomic walker. Evaluation showed enhanced comfort and postural support for users. Training modules for staff increased the organization’s capacity. The program exemplified how inclusive design and technological innovation can enhance therapy effectiveness, affordability, and sustainability.